2014
DOI: 10.1111/brv.12095
|View full text |Cite
|
Sign up to set email alerts
|

The ecophysiology of seed persistence: a mechanistic view of the journey to germination or demise

Abstract: Seed persistence is the survival of seeds in the environment once they have reached maturity. Seed persistence allows a species, population or genotype to survive long after the death of parent plants, thus distributing genetic diversity through time. The ability to predict seed persistence accurately is critical to inform long-term weed management and flora rehabilitation programs, as well as to allow a greater understanding of plant community dynamics. Indeed, each of the 420000 seed-bearing plant species ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
424
0
20

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(496 citation statements)
references
References 402 publications
(595 reference statements)
11
424
0
20
Order By: Relevance
“…Accordingly, the factor "prechilling" was included in the model, as prechilling is particularly suitable to break the physiological dormancy (Long et al, 2014). The results confirmed that prechilling has a positive effect on the germination capacity.…”
Section: Effect Of Various Prechilling Variants On Germinationmentioning
confidence: 68%
See 1 more Smart Citation
“…Accordingly, the factor "prechilling" was included in the model, as prechilling is particularly suitable to break the physiological dormancy (Long et al, 2014). The results confirmed that prechilling has a positive effect on the germination capacity.…”
Section: Effect Of Various Prechilling Variants On Germinationmentioning
confidence: 68%
“…If seeds have physiological dormancy, alternating temperatures can be used to break their dormancy (Long et al, 2014). Temperature had the greatest effect on germination capacity over all the five factors in our experiment.…”
Section: Effect Of Various Temperatures On Germinationmentioning
confidence: 80%
“…Em sua maioria, as espécies dessas famílias são herbáceas e pioneiras, produzem elevada densidade de diásporos e formam banco de sementes persistente (LONG et al, 2015).…”
Section: Discussionunclassified
“…The species composition in these grasslands varies between years, depending on previous seed production, dormancy and germination. These are all processes strongly influenced by climatic conditions such as temperature and moisture, and therefore most likely affected by climate change (Ooi, 2012;Cosentino et al, 2014;Long et al, 2015).…”
Section: Forage Quality and Species Compositionmentioning
confidence: 99%
“…when plants survive the dry summer as seeds; Long et al, 2015) and hardseededness (which allows a more persistent seed bank; Taylor, 2005) are the main adaptive strategies of annual species in Mediterranean grasslands. Based on the predicted changes in precipitation, with an overall reduced growth period in the driest Mediterranean regions, annual species will need earlier seed maturation for reliable seed set in shorter growing seasons, as well as mechanisms (i.e.…”
Section: Breeding For the Future Climatementioning
confidence: 99%